Scanning & analysing individual bee (Apis mellifera L.) behavior using RFID - van Praagh, Jacob P.; Touw, Egbert (Julius-Kühn-Archiv, 2012)
A complete system to make real-time flight entrance observations possible is described. The system consists of:a.RFID reader covering the flight entrance of a colony in a standard hive (25 cm wide). Each passing tagged bee is detected. ID, day, time is stored in the database and shown via the webinterface.b. ApiScan covering the same entrance width; giving in and out flight-activity on an individual basis.c. Camera allowing a permanent remote observation and registration of behavior at the flight entrance.d. Weather station registering air temperature, air humidity, wind velocity and direction, rain. The equipment and the data storage allows an in-depth analysis of the flight behavior of the worker bees during the measuring period or the lifespan of a worker bee.